(untitled) (European Journal of Child Development, Education and Psychopathology, 2019)
A correlational descriptive study is carried out to evaluate the relationship between the multiple intelligences of high school students in an integrated music center and their academic performance in musical and general matters, to check if the stimulation of intelligence and musical talent has positive influence in academic performance. To this end, the Yuste Hernanz general and factorial intelligence test (1991), Pozar’s survey of techniques and study habits (IHE) (1994), the IMCUIM questionnaire (Aliaga et al. al., 2012) of multiple intelligences and the academic qualifications of 2 continuous evaluations have been collected. The results allow to conclude that, in general, the results of the students in the subjects have been optimal in both the general and the musical modalities. It has been proven that these students have an above-average intellectual level and stand out for distinguishing multiple intelligences, such as musical, kinesthetic and interpersonal, so it is concluded that not only stimulate musical intelligence does not harm the academic performance, but, quite possibly, contributes to improving it.